Tinjauan Yuridis Pelaksanaan Perjanjian Jual Beli Bahan Bangunan Antara PT. Bale Citra Lestari (Depo Jaya Bangunan) Dengan Kontraktor - Ni Putu Wimas Lestari Dewi; Lalu Hadi Adha; M. Yazid Fathoni (Fakultas Hukum Universitas Mataram, 2023)
The purpose of this study is to find out the implementation and obstacles of the sale and purchase agreement of building materials between PT Bale Citra Lestari (Depo Jaya Bangunan) and the contractor providing building materials. The type of his research is normative-empirical legal research. The results indicated that PT Bale Citra Lestari (Depo Jaya Bangunan) and the contractor conducted (made) a written non-standard sale and purchase agreement for building materials based on the trust of the parties and only had a note or invoice as proof of payment. The contractor bought some building materials using a term payment system, but until now the contractor has not paid the remaining terms due to several obstacles outside the agreement that has been contracted, so the contractor is in default.